Characterization of silicate scale formation: the effect of pH on silicate scale formation mechanism - Mohd Yazid, Muhammad Farid (2019)
One of the challenging situations or problems that engineers nowadays have been encountering in oil and gas industry is the formation of silicate scale. ASP flooding is one of the methods used to improve the oil recovery efficiency, however this technique could produce the silicate scale which apparently are difficult to be removed once they formed. Frequent shut down for cleaning and maintenance not only costing more money, but also will causing loss in profit as the production and process need to be stopped during maintenance. Initially, the ASP sludge was injected into the reservoir at high pH value and this condition will silica dissolution in the sandstone reservoir. As it propagating within the reservoir from the injection well to the production well, it will mix up with the connate water that is essentially at neutral pH. The mixing of these waters resulted in reduced pH condition inside the reservoir which will reduce the solubility of silica. Supersaturation condition is achieved and will induce the formation of silicate scale formation. Silicate scale is pH dependent scale type and it is postulated that different type and morphology will be produced with the variation of pH. In this work, duplicate samples were prepared to reproduce the ASP leachate by mixing the magnesium brine to represent the connate water (low pH) with silica brines that represent ASP sludge (high pH). The first duplicate sample was pH adjusted to pH 8.5 and left reacted at room temperature for 22 hours. Another duplicate sample was left reacted at its mixed pH of approximately ~11, room temperature for the same duration. The third duplicate sample was reacted at the same condition as the second duplicate before being pH adjusted to pH 8.5 at 22 hours and left reacted for another 22 hours. All precipitate produced from these three reaction condition were filtered and analyzed using Fourier‟s Transformation Infra-Red (FTIR) and X-ray Diffraction (XRD) to characterize the samples. The pure commercial samples which were magnesium silicate, magnesium hydroxide and silicon dioxide were also analyzed as a comparison to the produced precipitate. Sample in lower initial pH condition demonstrated a XRD pattern with higher intensity, sharp peak and also longer diffraction signals distance indicates that the scale is crystalline. FTIR spectra confirmed the presence of Si-O covalent bond and Si-O-Si stretching and SiO-Mg functional group in all three conditions. Results clearly show that pH will affect the type and morphology of precipitate significantly and the precipitates were able to be characterized by using the spectroscopic analysis.